2015
DOI: 10.2340/00015555-2051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Moisturizing Creams for the Prevention of Atopic Dermatitis Relapse: A Randomized Double-blind Controlled Multicentre Clinical Trial

Abstract: Atopic dermatitis (AD) affects adults and children and has a negative impact on quality of life. The present multicentre randomized double-blind controlled trial showed a barrier-improving cream (5% urea) to be superior to a reference cream in preventing eczema relapse in patients with AD (hazard ratio 0.634, p = 0.011). The risk of eczema relapse was reduced by 37% (95% confidence interval (95% CI) 10-55%). Median time to relapse in the test cream group and in the reference cream group was 22 days and 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 27 publications
5
69
0
4
Order By: Relevance
“…Four studies compared urea versus plain emollients (water-oil emulsions without urea or other 'active' substances): three in adults with AD [28,29,32] and one in patients with IV [30]. In 172 patients whose AD lesions had been cleared by means of corticosteroids, 6 months of treatment with urea 5 % significantly prolonged the time to relapse (HR 0.63, p = 0.011) [32].…”
Section: Ureamentioning
confidence: 98%
See 2 more Smart Citations
“…Four studies compared urea versus plain emollients (water-oil emulsions without urea or other 'active' substances): three in adults with AD [28,29,32] and one in patients with IV [30]. In 172 patients whose AD lesions had been cleared by means of corticosteroids, 6 months of treatment with urea 5 % significantly prolonged the time to relapse (HR 0.63, p = 0.011) [32].…”
Section: Ureamentioning
confidence: 98%
“…In 172 patients whose AD lesions had been cleared by means of corticosteroids, 6 months of treatment with urea 5 % significantly prolonged the time to relapse (HR 0.63, p = 0.011) [32]. In the other two AD studies, urea 4 % was merely used as a positive control, and no formal comparison was made between urea and plain emollient [28,29].…”
Section: Ureamentioning
confidence: 98%
See 1 more Smart Citation
“…Concentrations less than 10% were not tested in this particular study; however, formulations containing 5% urea have been shown to strengthen the skin barrier in a series of other studies [45,46]. Moreover the barrier-strengthening properties of the emollients were linked to the ability of the emollients to delay relapses of both AD and hand eczema in young adults [13,47,48,49]. The results of this study further demonstrate that a distinct 5% urea preparation with ceramide NP and lactate also imparts positive effects on skin barrier function and SC integrity in an older population.…”
Section: Discussionmentioning
confidence: 99%
“…They have reached epidemic proportions worldwide and their incidence is continuing to increase in association with modern lifestyles3. The mechanism underlying the recurrence of allergic diseases is far from resolved456, making it urgent to explore the mechanisms of allergic diseases and to develop new drugs that effectively reduce the rate of recurrence.…”
mentioning
confidence: 99%